Application of titanium dioxide as glass clarifying agent and in borosilicate glass clarification
By adding 2-6% titanium dioxide to the raw materials of borosilicate glass, the difficulty of clarification during the melting of borosilicate glass is solved, and a more efficient clarification process and better quality glass liquid is achieved, and it has environmentally friendly and economical advantages.
Patent Information
- Application Number
- CN202411804774.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
Borosilicate glass is difficult to clarify during melting, resulting in high production costs and poor quality of the glass liquid.
Add 2-6% titanium dioxide to the raw material of borosilicate glass, as a glass clarification agent, and melt it with the raw material to promote the clarification of the glass.
Titanium dioxide significantly shortens the clarification time of borosilicate glass, reduces the viscosity and clarification difficulty of the glass liquid, and improves the clarification efficiency. It is more environmentally friendly, non-toxic and cheaper than traditional clarification agents.
Smart Images

Figure CN119612955A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a new use of titanium dioxide, in particular to an application of titanium dioxide as a glass clarifier, and also to an application of titanium dioxide in the clarification of borosilicate glass, belonging to the technical field of glass production. Background Art
[0002] Alkali borosilicate glass has [BO 4 ] can connect the broken networks in the silicon-oxygen network and improve the integrity of the glass network. Therefore, it has a lower thermal expansion coefficient and better chemical stability and thermal stability than soda-lime-silica glass, and therefore has better application prospects in the fields of heat-resistant utensils, optical materials and medical packaging materials.
[0003] The preparation process of alkali borosilicate glass is as follows: silica sand, soda ash, boric acid, borax and other raw materials are made into ingredients, the ingredients are melted in a flame kiln or an electric melting furnace, and go through the stages of silicate formation, glass formation, glass liquid clarification, and homogenization to form a glass liquid with no visible bubbles whose temperature and viscosity meet the molding requirements (these are the five stages of the glass melting process), and finally it is formed manually or mechanically to form the final glass product. In the early stage of melting of borosilicate glass, most of the gases entrained through the gaps between powder particles in the glass batch and the gases formed by the decomposition of raw materials such as soda ash, boric acid, borax, calcium carbonate, and aluminum hydroxide have been discharged with the flue gas in the early stage of glass melting (mainly the silicate formation stage). A small part remains in the above-mentioned glass formation stage and remains on the surface or inside the glass liquid to form a foam layer (for flame radiation heating furnaces, the foam layer is located before the bubble boundary of the furnace, and for electric melting furnaces, it is located below the cold top batch). These bubbles naturally burst or rise and disappear as the melting time increases. What finally remain in the glass liquid are a small amount of visible bubbles and gases dissolved in the glass liquid; usually the glass liquid clarification process is to remove the small amount of visible bubbles remaining in the glass liquid. In actual production, the clarification process occurs after the bubble boundary, i.e., in the flameless zone (i.e., the clarification section) of the flame pool kiln glass pool kiln or in the lower part of the electric melting furnace. The silicon oxide content in borosilicate glass exceeds 70wt%, and the B 2 O 3 When the content exceeds 10wt%, the glass generally has high viscosity, which makes it difficult to clarify the glass liquid. Therefore, it takes a long time to clarify borosilicate glass, and the difficulty of clarification has always plagued the production of this type of glass. Finding a suitable clarifier and shortening the clarification stage time of the borosilicate glass melting process is very important for reducing production costs and improving the quality of glass liquid.
[0004] In order to accelerate the clarification process of the glass melt and eliminate the visible bubbles remaining in the glass melt, physical stirring, increasing the clarification temperature, adding clarifiers and other methods can be used. Since the first two methods consume a lot of energy and are not conducive to industrial production and environmental protection, adding a suitable clarifier is the best choice. In the industrial production of alkali borosilicate glass, As 2 O 3 , Sb 2 O 3 and NaCl or its complex as clarifiers. However, they are harmful to the environment, such as NaCl releases chlorine-containing waste gas, and As and Sb are toxic, especially cannot be used in the production of glassware such as food and medicine contact. In recent years, new rare earth oxides have been reported, such as CeO 2 Although the clarification effect is good, it is expensive and a small amount of addition can increase the high-temperature viscosity of the melt, which is not conducive to glass production. Summary of the invention
[0005] The inventors found in the experiment that titanium dioxide can shorten the clarification time of borosilicate glass melt and reduce the clarification start temperature of the glass melt, thus promoting the clarification of borosilicate glass. 2 TiO can play a clarifying role in borosilicate glass, on the one hand, because 2 The addition of Ti reduces the high-temperature viscosity of the glass melt, which is conducive to the merging and growth of bubbles, and finally floats to the surface of the glass and disappears; on the other hand, the Ti ions in the glass 4+ and Ti 3+ Two valence states, so it is speculated that the added TiO 2 In high temperature glass melt, there is a reaction process from high valent oxide to low valent oxide, which is the same as that of traditional arsenic and antimony clarifiers, namely, Ti 4+ →Ti 3+ +O 2 The decomposition reaction produces O 2 It merges into the existing bubbles in the glass liquid, promotes the growth and floating of small bubbles, and plays a role in accelerating clarification.
[0006] Based on the above findings, the present invention provides an application of titanium dioxide as a glass clarifier, especially as a borosilicate glass clarifier, wherein the titanium dioxide is added together with the raw materials of the borosilicate glass for melting, rather than being added during the glass clarification stage.
[0007] The present invention also provides an application of titanium dioxide in the clarification of borosilicate glass, specifically: titanium dioxide is added to borosilicate glass as a glass clarifier to shorten the melting and clarification process of borosilicate glass and reduce the melting and clarification temperature of glass. Titanium dioxide is directly added to borosilicate glass raw materials, mixed with the raw materials and then added to melt.
[0008] Furthermore, the amount of titanium dioxide used is 2-6% of the total mass of the borosilicate glass raw material, such as 2%, 3%, 4%, 5%, 6%.
[0009] A method for preparing borosilicate glass, the method comprising the following steps:
[0010] (1) Selecting glass raw materials according to the designed composition of borosilicate glass;
[0011] (2) selecting titanium dioxide as a glass clarifier, and uniformly mixing various glass raw materials and titanium dioxide to obtain a glass batch;
[0012] (3) heating and melting the glass batch materials to obtain molten glass;
[0013] (4) pouring the glass liquid into a mold to form it, and then annealing the formed glass, and cooling it to room temperature after annealing to obtain borosilicate glass.
[0014] Furthermore, the borosilicate glass can be any borosilicate glass with any boron and silicon content, and is particularly suitable for medium-alkali medium-borosilicate glass with a silicon dioxide content of 70% or more, a boron oxide content of 10% or more, and an alkali content of 6% to 12%. Compared with low-borosilicate glass, the glass liquid obtained from medium-alkali medium-borosilicate glass has a higher viscosity, is more difficult to clarify, and takes a long time; compared with high-borosilicate glass, medium-alkali medium-borosilicate glass has a higher alkali content, produces more bubbles, and is more difficult to clarify.
[0015] In a specific embodiment of the present invention, the borosilicate glass is designed to have a composition of: SiO 2 72~75wt%,Na 2 O 7~12wt%, B 2 O 3 11.5~12wt%,Al 2 O 3 2.5~4.6wt%, ZnO 0~1wt%, CaO 0.5~0.8wt%, the sum of all ingredients is 100wt%.
[0016] Furthermore, the borosilicate glass with the above-mentioned composition is made of quartz sand, sodium carbonate, borax, aluminum hydroxide, zinc oxide and calcium carbonate, wherein: SiO 2 Introduced by quartz sand, Na 2 O is introduced by sodium carbonate, B 2 O 3 Introduced by borax, Al 2 O 3It is introduced by aluminum hydroxide, ZnO is introduced by zinc oxide, and CaO is introduced by calcium carbonate.
[0017] Furthermore, the amount of titanium dioxide added is 2-6% of the total mass of all glass raw materials, such as 2%, 3%, 4%, 5%, 6%. Titanium dioxide is directly introduced in the form of oxide.
[0018] Furthermore, in step (3), the glass batch material is heated to 1550-1650°C for melting, for example, 1550°C, 1600°C, 1650°C, and kept warm until the glass liquid is clear and free of bubbles. The melting time varies depending on the amount of batch material used.
[0019] Furthermore, in step (4), the annealing temperature is 500-600° C., such as 500° C., 550° C., or 600° C., and preferably, the annealing time is 1-2 hours.
[0020] The present invention has the following beneficial effects:
[0021] 1. In the present invention, titanium dioxide is added during the preparation process of borosilicate glass. Titanium dioxide is added to the glass batch material and melted together with the glass raw materials. Experimental results show that titanium dioxide can significantly promote the clarification of the glass, shorten the time of glass clarification, significantly reduce bubbles in the glass liquid, improve the clarification efficiency, and reduce the viscosity of the glass liquid and the difficulty of clarification.
[0022] 2. The present invention uses cheap TiO 2 Replace traditional As, Sb, NaCl and rare earth CeO 2 As a clarifier for medium-alkali borosilicate glass, TiO 2 When the content is higher than 4wt%, a good clarification effect can be achieved, the clarification time can be shortened and the viscosity of the glass liquid can be reduced. Compared with the existing clarifiers, the titanium dioxide of the present invention is more environmentally friendly, non-toxic and has a lower price, and is expected to contribute to the environmental protection and energy saving of borosilicate glass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 For different TiO 2 High-temperature visual image of the melt when the amount is added is kept at 1550℃ for 30min.
[0024] Figure 2 This is a graph showing the change in viscosity of the glass melt with different amounts of titanium dioxide added as the temperature increases in Example 1.
[0025] Figure 3 TiO 2 X-ray photoelectron spectrum of the glass sample obtained when the content is 4wt%.
[0026] Figure 4 For different TiO 2 High temperature image of the melt at 1550℃ for 30min when adding the amount of TiO 2 -0%, (b) TiO 2 -4%.
[0027] Figure 5 For different TiO 2 High temperature image of the melt at 1550℃ for 10 min when adding the amount of TiO 2 -0%, (b) TiO 2 -4%, (c) TiO 2 -6%.
[0028] Figure 6 For different TiO 2 High-temperature visual image of the melt at 1650℃ for 30min when the amount of added TiO 2 -0%, (b) TiO 2 -6%.
[0029] Figure 7 This is a graph showing the change in viscosity of the glass melt with different amounts of titanium dioxide added as the temperature increases in Example 4. DETAILED DESCRIPTION
[0030] The following is a description of exemplary embodiments of the present invention, including various details of the embodiments of the present invention to aid understanding, which should be considered as merely exemplary. Therefore, it should be appreciated by those of ordinary skill in the art that various changes and modifications may be made to the embodiments described herein without departing from the scope and spirit of the present invention. Likewise, for clarity and simplicity, descriptions of well-known functions, operations, and structures are omitted in the following description.
[0031] Example 1
[0032] (1) The basic glass components (wt%) are designed as follows: SiO 2 72,Na 2 O 12,B 2 O 3 12,Al 2 O 3 2.5, ZnO 1, CaO0.5.
[0033] (2) Select glass raw materials according to the above glass components, wherein the glass raw materials are: quartz sand, sodium carbonate, borax, aluminum hydroxide, zinc oxide, and calcium carbonate, and each raw material is an analytical grade reagent.
[0034] (3) Weigh the raw materials according to the required formula weight of 100g of glass liquid, and add 0%, 2%, 3%, 4%, and 6% of titanium dioxide as a clarifier to the glass raw materials based on the total weight of the glass raw materials. Titanium dioxide (anatase) is an analytical grade reagent.
[0035] (4) The glass raw materials and titanium dioxide were mixed uniformly, and then the temperature was raised to 1550° C. at a rate of 5° C. / min using a muffle furnace, and then kept at this temperature for 30 min.
[0036] A high temperature video system was used to observe the addition of different amounts of TiO 2 The bubble removal of the melt obtained by keeping the glass batch at 1550℃ for 30 minutes is used to judge the clarification effect of the glass liquid based on the number of bubbles in the field of view. Figure 1 As shown, from left to right TiO 2 The content of TiO 2 208 of the -0% samples were reduced to TiO 2 -6% of the samples. Among them, TiO 2 When the content is 2wt%, the number of bubbles is reduced by half (from 208 to 117) compared with 0wt%. 2 When the content increases from 2wt% to 3wt%, the number of bubbles decreases slowly (from 117 to 110). 2 When the content increases from 3wt% to 4wt%, the number of bubbles decreases rapidly (from 110 to 2), and there are no bubbles at all when the content reaches 6wt%. 2 The addition of can significantly reduce the number of bubbles and shorten the clarification time.
[0037] TiO 2 The reason why TiO can play a clarifying role in borosilicate glass is that 2 The addition of reduces the high temperature viscosity of the glass melt (such as Figure 2 As shown), it is conducive to the merging and growth of bubbles, and finally they float to the surface of the glass and disappear. On the other hand, the experiment confirms that the Ti ions exist in the glass. 4+ and Ti 3+ Two valence states (such as Figure 3 As shown), it is speculated that the added TiO 2 In high temperature glass melt, there is a reaction process from high-valent oxide to low-valent oxide, which is the same as that of traditional arsenic and antimony clarifiers, namely, T i4+ →Ti 3+ +O 2 The decomposition reaction produces O 2 It merges into the existing bubbles in the glass liquid, promoting the growth and floating of small bubbles, thereby playing a clarifying role.
[0038] Example 2
[0039] (1) The basic glass components (wt%) are designed as follows: SiO 2 72,Na 2 O 12,B 2 O 3 12,Al 2 O 3 2.5, ZnO 1, CaO0.5.
[0040] (2) Select glass raw materials according to the above glass components, wherein the glass raw materials are: quartz sand, sodium carbonate, borax, aluminum hydroxide, zinc oxide, and calcium carbonate, and each raw material is an analytical grade reagent.
[0041] (3) Weigh each raw material according to the formula weight required for 100 g of glass liquid, and add 4% of the total weight of titanium dioxide as a clarifier to the glass raw materials. Titanium dioxide (anatase) is an analytical grade reagent.
[0042] (4) The glass raw materials and titanium dioxide were mixed uniformly, and then the temperature was raised to 1550° C. at a rate of 5° C. / min using a muffle furnace, and then kept at this temperature for 30 min to obtain glass liquid.
[0043] (5) The glass liquid is taken out at high temperature and poured onto a preheated copper mold for forming. The glass liquid is then transferred to an annealing furnace and annealed at 550°C for 2 hours. After annealing, the glass liquid is cooled to room temperature and taken out to obtain borosilicate glass.
[0044] Use a high temperature video camera to observe the bubble growth and elimination process, such as Figure 4 As shown in the figure, after the glass was kept at 1550℃ for 30min, the number of bubbles was reduced to 2, which was similar to that without adding TiO. 2 In the glass melt, the number of bubbles is significantly reduced.
[0045] Example 3
[0046] (1) The basic glass components (wt%) are designed as follows: SiO 2 72,Na 2 O 12,B 2 O 3 12,Al 2 O 3 2.5, ZnO 1, CaO0.5.
[0047] (2) Select glass raw materials according to the above glass components, wherein the glass raw materials are: quartz sand, sodium carbonate, borax, aluminum hydroxide, zinc oxide, and calcium carbonate, and each raw material is an analytical grade reagent.
[0048] (3) Weigh each raw material according to the formula weight required for 100 g of glass liquid, and add 4% and 6% of titanium dioxide as a clarifier to the glass raw materials based on the total weight of the glass raw materials. Titanium dioxide (anatase) is an analytical grade reagent.
[0049] (4) The glass raw materials and titanium dioxide were mixed uniformly, and then the temperature was raised to 1550° C. at a rate of 5° C. / min using a muffle furnace, and then kept at this temperature for 10 min to obtain glass liquid.
[0050] (5) The glass liquid is taken out at high temperature and poured onto a preheated copper mold. The glass liquid is then transferred to an annealing furnace and annealed at 550°C for 2 hours. After annealing, the glass liquid is cooled to room temperature and taken out to obtain borosilicate glass.
[0051] Use a high temperature video camera to observe the bubble growth and elimination process, such as Figure 5 As shown in the figure, after the glass was kept at 1550℃ for 10min, the number of bubbles in the glass melt with 6% titanium dioxide was completely eliminated, which was different from that without adding TiO 2 Compared with the glass melt with 4% titanium dioxide added, the number of bubbles in the glass melt is significantly reduced and the bubble elimination time is shorter.
[0052] Example 4
[0053] (1) The basic glass components (wt%) are designed as follows: SiO 2 75,Na 2 O 8,B 2 O 3 11.6,Al 2 O 3 4.6,CaO 0.8.
[0054] (2) Select glass raw materials according to the above glass components, wherein the glass raw materials are: quartz sand, sodium carbonate, borax, aluminum hydroxide, and calcium carbonate, and each raw material is an analytical grade reagent.
[0055] (3) Weigh each raw material according to the formula weight required for 100 g of glass liquid, and add 6% of the total weight of titanium dioxide as a clarifier to the glass raw materials. Titanium dioxide (anatase) is an analytical grade reagent.
[0056] (4) The glass raw materials and titanium dioxide were mixed uniformly, and then the temperature was raised to 1650° C. at a rate of 5° C. / min using a muffle furnace, and then kept at this temperature for 30 min to obtain molten glass.
[0057] (5) The glass liquid is taken out at high temperature and poured onto a preheated copper mold. The glass liquid is then transferred to an annealing furnace and annealed at 600°C for 2 hours. After annealing, the glass liquid is cooled to room temperature and taken out to obtain borosilicate glass.
[0058] Use a high temperature video camera to observe the bubble growth and elimination process, such as Figure 6 As shown in the figure, after the glass was kept at 1650℃ for 30min, the number of bubbles in the glass melt with 6wt% TiO2 was only 10, which was significantly lower than that without TiO2. 2 Compared with the glass melt, the number of bubbles is significantly reduced. 2 After that, the high temperature viscosity of the glass melt decreased significantly. Figure 7 shown.
Claims
1. Application of titanium dioxide as glass clarifier.
2. The use according to claim 1, characterized in that: The glass is borosilicate glass.
3. The application of titanium dioxide in the clarification of borosilicate glass is characterized by: It is added to borosilicate glass as a glass clarifier.
4. The use according to claim 3, characterized in that: Titanium dioxide is added to the borosilicate glass raw material.
5. The use according to claim 3, characterized in that: The amount of titanium dioxide used is 2-6% of the total mass of the borosilicate glass raw material.
6. A method for preparing borosilicate glass, characterized in that The following steps are involved: (1) Selecting glass raw materials according to the designed composition of borosilicate glass; (2) selecting titanium dioxide as a glass clarifier, and uniformly mixing various glass raw materials and titanium dioxide to obtain a glass batch; (3) heating and melting the glass batch materials to obtain molten glass; (4) pouring the glass liquid into a mold to form it, and then annealing the formed glass, and cooling it to room temperature after annealing to obtain borosilicate glass.
7. The method according to claim 6, characterized in that: The amount of titanium dioxide added is 2-6% of the total mass of all glass raw materials.
8. The method according to claim 6 or 7, characterized in that: The designed composition of borosilicate glass is: SiO2 72-75wt%, Na2O 7-12wt%, B2O3 11.5-12wt%, Al2O3 2.5-4.6wt%, ZnO 0-1wt%, CaO0.5-0.8wt%.
9. The method according to claim 8, characterized in that: SiO2 is introduced from quartz sand, Na2O is introduced from sodium carbonate, B2O3 is introduced from borax, Al2O3 is introduced from aluminum hydroxide, ZnO is introduced from zinc oxide, and CaO is introduced from calcium carbonate.
10. The method according to claim 6 or 7, characterized in that: In step (3), the temperature is raised to 1550-1650°C for melting to obtain glass liquid; in step (4), the annealing temperature is 500-600°C.